The Brazilian Sign Language: overview, limits and perspectives about its insertion as a communication mechanism for the deaf in school and society (Research, Society and Development, 2021)
This present work presents a general view on the inclusion of the Brazilian Sign Language in public schools and society as an instrument of communication of the deaf, whether among the deaf community itself or between deaf and hearing people. The Brazilian Sign Language, without a doubt, is a great achievement by the deaf with regard to their emancipation as a subject of rights situated in a historical and social context. The school is legitimizing both inclusion and the opposite process, and society walks together in this itinerary as a space for struggles and also for great achievements. In this sense, it is point out some legal aspects about sign language, its role as a public policy for the deaf and its situational framework in the Brazilian context as a sign of progress, but also of large gaps that still need to be filled in order for the it reaches its effectiveness in educational and training spaces. Thus, progress could be verified in relation to entering the deaf in school and improvements such as the training of professionals, presence of interpreters and affirmation of existing legislation regarding this cause, however, there is still much to be done, and for this, it is necessary the due attention of public policies to consolidate the Brazilian sign language as a communication and interaction mechanism for the deaf with the school and society.